1977
DOI: 10.1002/jcp.1040930118
|View full text |Cite
|
Sign up to set email alerts
|

Transformed BHK cells exhibiting normal or subnormal sugar uptake

Abstract: The uptake of deoxyglucose was compared in BHK cells and in DMN4B cells, a conditionally transformed line of BHK cells which exhibits transformed behavior a t 38.5' but not at 32'. At 32', DMN4B cells took up deoxyglucose more slowly than BHK cells, reflecting a higher Km for uptake of this sugar. When both cell lines were grown at 38.5', the Km for DMN4B cells was reduced to a level only slightly greater than for BHK cells, and deoxyglucose uptake became similar in the two cell lines. Growth in glucose-free m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1981
1981
1986
1986

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Loss of control over glucose (or other substrates) transport, a widespread phenomenon occuring in transformed cells [33,77,1261, was responsible and the excess glucose taken up was wasted through overproduction and secretion of lactate during the course of the batch culture. It has also been observed that, with this particular cell cultivation procedure, the non-growth-associated utilization of glucose can be reduced and the cell yields can be improved when the addition of glucose is automatically controlled by fed-batch methods.…”
Section: Choice Of Proper Cultivation Methodsmentioning
confidence: 99%
“…Loss of control over glucose (or other substrates) transport, a widespread phenomenon occuring in transformed cells [33,77,1261, was responsible and the excess glucose taken up was wasted through overproduction and secretion of lactate during the course of the batch culture. It has also been observed that, with this particular cell cultivation procedure, the non-growth-associated utilization of glucose can be reduced and the cell yields can be improved when the addition of glucose is automatically controlled by fed-batch methods.…”
Section: Choice Of Proper Cultivation Methodsmentioning
confidence: 99%